MMP-2 and MMP-9 in lymph-node-positive bladder cancer. Issue 12 (21st June 2011) - Seiler, Roland; Thalmann, George N; Fleischmann, Achim
Abstract : Background: Matrix metalloproteinases (MMP), particularly MMP-2 and MMP-9, participate in tumour progression and metastasis in various cancers. Their significance in urothelial cancer of the bladder (UCB) is unclear. Expression analysis of MMP-2 and MMP-9 in tissue microarrays (TMA) constructed of corresponding samples from histopathological normal urothelium, tumour centre and invasion front of primary tumours and lymph-node (LN) metastases might help to elucidate their relevance in UCB. Method: MMP-2 and MMP-9 expression was evaluated in TMA of 150 surgically treated LN-positive UCB patients. Biomarker expression was correlated with tumour characteristics (primary tumour and LN stage, number, total diameter and extracapsular extension of LN metastases) and overall survival. Results: While there was a significant increase in MMP-9 expression from normal urothelium over primary tumours to metastases (median scores: 20, 50, 65; p<0.005), no such trend was observed in MMP-2 (median scores: 5, 22, 10; p<0.005). A comparison of expression in the tumour centre and the invasion front showed no difference in both MMP. No association between expression and histopathological tumour characteristics was identified. There was a non-significant trend for a more favourable outcome for patients with high MMP-2 expression in primary tumours. Conclusion: In LN-positive UCB, MMP-2 and MMP-9 expression was not increased at the invasion front, suggesting an infiltration strategy independent of MMP-2 and MMP-9 activity. Larger series are needed to detect a potential significant trend for favourable outcome in cancers with high MMP-2 expression.